Corporate strategies, freight transport and regional development - Alain Thierstein; Klaus-Dieter Schnell (European Regional Science Association (ERSA), 1998)
Corporate strategies and decisions concerning location, such as outsourcing of individual production processes, have an impact on the volume of freight traffic. Due to concentration of core competences, new logistics trends, growing importance of services and liberalization of markets, corporate strategies undergo rapid changes. Their spatial impact is of interest, especially when taking into account that new corporate behaviour can increase as well as reduce freight traffic. The overall impact of these changes are very unclear and little empirical evidence is available besides various insights from networks in the automotive sector. For example reducing the level of in-house production may multiply the number of suppliers. They in turn deliver the required parts more frequently but in smaller batches thus increasing the volume of freight transportation. On the other hand the manifest trend towards the concentration and bundling of single suppliers in the form of component or systems suppliers tends to reduce freight traffic for production inputs. The paper examines two key aspects. First it sheds light on the interrelationships of structural changes of the economy, in particular of corporate behaviour (e.g. outsourcing, just-in-time production, telecommunications) and the volume of freight traffic. Second we will try to answer the following question: in what types of companies does the division of labour along the chain of value added lead to increased freight traffic and where can freight traffic be reduced by means of telematics. The paper draws from an empirical study of a region in Central Switzerland. Recommendations for public as well as private actors will deal with potentials to reduce freight traffic through cooperative efforts.
Keywords: 330